The Role of Social Media as a Micro-Ecosystem in Supporting Community-Based E-Learning Platforms: A Systematic Literature Review - Agustin, Naila; Rahayu, Septi (University of Science and Computer Technology, 2025)
This study explores the role of social media as a micro-ecosystem that supports community-based E-learning, adopting a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. From 450 screened publications, 80 relevant studies were analysed using both qualitative thematic synthesis and descriptive meta-analysis. The findings reveal that social media platforms, such as WhatsApp, Facebook, YouTube, and Discord, enhance collaboration, engagement, and learning motivation, with average improvements of about 40% in learner participation and 98% in message openness, based on aggregated quantitative evidence from prior research. The review also identifies significant challenges, including digital distraction, privacy risks, and limited digital literacy, which can reduce the effectiveness of social-media-based learning. By integrating adaptive learning algorithms, AI-driven analytics, and privacy-by-design principles, the study conceptualises social media as an intelligent, ethically grounded, and sustainable learning micro-ecosystem aligned with informatics and systems-engineering perspectives.